2003
DOI: 10.1046/j.1440-0979.2003.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions of mental health assessment in an acute inpatient setting in New Zealand: A qualitative study

Abstract: This qualitative study explores the perceptions of mental health nurses regarding assessment in an acute adult inpatient setting in Central Auckland. Fourteen mental health nurses took part in semistructured interviews answering five open-ended questions. The analysis of data involved a general inductive approach, with key themes drawn out and grouped into four categories (roles, attitudes, skills and knowledge) in order to explore the meaning of information gathered. The outcome of the study acknowledged the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…In the present study, nurses' perceptions of their role in risk assessment was more clearly delineated than previous studies (Bishop & Ford-Bruins, 2003). This may relate to a stronger role and expectation of nurse involvement in the multidisciplinary team in this service.…”
Section: Discussioncontrasting
confidence: 58%
“…In the present study, nurses' perceptions of their role in risk assessment was more clearly delineated than previous studies (Bishop & Ford-Bruins, 2003). This may relate to a stronger role and expectation of nurse involvement in the multidisciplinary team in this service.…”
Section: Discussioncontrasting
confidence: 58%
“…Crawford et al () highlight a point of tension between mental health nurses assuming the identity of a ‘Jack of all trades’ and the need to accomplish a clear professional identity. The term ‘Jack of all trades’ has been used by mental health nurses themselves about their professional identity in studies in Australia (Cleary, ), New Zealand (Bishop & Ford‐Bruins, ), and the UK (Crawford et al , ; Skidmore, Warne & Stark, ). The maxim ‘Jack of all trades and Master of none’ has been considered to reflect the low status with which mental health nursing has sometimes been viewed (McCabe, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study [1] it is indicated that mental health nurses working in acute inpatient settings experience a need for adjustment regarding their role in the assessment process of treatment. A cornerstone in nursing practice is to adopt a holistic patient perspective, taking into account not only the patient's pathology but also psychological and social factors.…”
Section: Introductionmentioning
confidence: 99%